Impact of limestone quarrying industries On the livelihood of the surrounding population : experience at Gunung Lengkun, Ipoh, Perak - Kamal, Kamarul’ain; Abdullah, Kamariah; Othman, Nor A’aini; Md Saman, Nor Hisham (2008)

(untitled)
The quarrying industry is one of Perak’s major economic base. It plays an important role in contributing towards the construction industry’s development by providing materials such as marble, granite, cement etc. Since many of the quarrying industries are operating within close proximity to the surrounding urban land uses (eg. housing and commercial areas, such as in the case of Gunung Lengkun in Ipoh, Perak), it is important that the quarrying activities are being carried out in a safe and environmentally friendly manner in order to create a sustainable urban development area. The study aims to identify the environmental and social impact issues arises due to the quarrying activities by assessing the perception of the communities living close to the quarrying sites. The focus of the study is mainly related to issues on the quality of the environment, family health condition, blasting effect and public safety. The study revealed that the main concerned of the communities are problems related to health condition and public safety. Therefore, the study recommends that the related authorities should continuously enforcing rules and guidelines as well as compliance monitoring to ensure that the quarry operators abide to the regulatory standard measures. This will help in improving the livelihood of the affected communities.